Prevalensi dan Intensitas Mikroplastik di Saluran Pencernaan Kerang Darah (Anadara granosa) Pada Ekosistem Estuari Pantai Jono Desa Lalang Kabupaten Batu Bara - Muhammad Farhan Pulungan; Mufti Sudibyo (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2025)
Microplastics have contaminated almost all living ecosystems, especially in aquatic ecosystems. microplastics can interfere with the growth of marine organisms, and the impact is quite serious. This study aims to determine the shape and color of microplastics, the prevalence (presence) of microplastics and the intensity (amount) of microplastics in the digestive tract organs (Anadara granosa). The research was conducted during September - October 2024, sampling was carried out in the estuary area of Jono Beach, Lalang Village, Batu Bara Regency, North Sumatra, 40 samples were taken each. Microplastic extraction was carried out by taking the clam's digestive tract, weighing it into a microtube and adding 10% KOH solution as much as 3: 1 with the weight of the tissue, closed and allowed to stand for 24 hours at 40°C. After 24 hours in the centrifuge for 2 minutes at 500 rpm to precipitate all particles dissolved in the liquid. The solution on top was discarded and the solids on the bottom were taken for examination under a microscope. The results showed that microplastics were found in the digestive tract of clams in the types of fragments (80%), fibers (17%) and films (3%). While the most dominant color of microplastics is black (74%), red (14%), blue (6%), clear (6%), and clear (6%).